2019
DOI: 10.18203/2394-6040.ijcmph20195065
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of antenatal care among mothers of infants in rural area of Belagavi: a cross sectional study

Abstract: Background: Antenatal care (ANC) is the care given to pregnant women for safe pregnancy and healthy babies. It is the most effective health intervention for preventing maternal morbidity and mortality. Health knowledge is an important element which enables women to be aware of their health status and promotes service utilization which further improves the health of the beneficiaries. This study was conducted among mothers of rural area of Belagavi with an objective to determine the level of knowledge related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“… 16 Educational status in our study was 90.75% and only 2.25% were working, which was in concordance with the previous studies. 10 , 17 Agarwal et al 18 found that ANC was very low for illiterate women and among those whose husbands were illiterate and nonskilled workers. These findings were similar to our findings where educated women were better acquainted with many aspects of prenatal care.…”
Section: Discussionmentioning
confidence: 99%
“… 16 Educational status in our study was 90.75% and only 2.25% were working, which was in concordance with the previous studies. 10 , 17 Agarwal et al 18 found that ANC was very low for illiterate women and among those whose husbands were illiterate and nonskilled workers. These findings were similar to our findings where educated women were better acquainted with many aspects of prenatal care.…”
Section: Discussionmentioning
confidence: 99%